A polycrystalline high-nickel ternary positive electrode material, a preparation method and application thereof

CN121546052BActive Publication Date: 2026-11-03GUANGDONG BRUNP RECYCLING TECH CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511743861.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-25
Publication Date
2026-11-03
Estimated Expiration
2045-11-25

AI Technical Summary

Technical Problem

High-nickel ternary cathode materials develop cracks during cycling due to volume expansion and contraction, leading to premature battery failure.

Method used

Polycrystalline high-nickel ternary cathode materials are prepared, with pores on the surface and inside of the material, and coated with conductive agents such as carbon nanotubes, flake graphite, conductive fibers or amorphous carbon. The material structure is optimized by controlling the porosity, pore size and lithium-nickel mixing ratio.

Benefits of technology

The pores provide space for material expansion, reducing breakage, while the conductive agent improves current conduction efficiency and enhances cycle performance and electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121546052B_ABST
    Figure CN121546052B_ABST
Patent Text Reader

Abstract

The application discloses a kind of polycrystal high-nickel ternary positive electrode materials and preparation method and application, belong to battery material technical field.The polycrystal high-nickel ternary positive electrode material includes polycrystal high-nickel ternary positive electrode material body, at least part surface and at least part internal area of polycrystal high-nickel ternary positive electrode material body have hole, at least the surface of polycrystal high-nickel ternary positive electrode material body has conductive agent.The hole in the polycrystal high-nickel ternary positive electrode material can reserve space for material expansion in the process of circulation, can reduce material crushing, enhance material cycle performance;In addition, conductive agent at least exists in the surface of polycrystal high-nickel ternary positive electrode material body, not only conducive to stabilizing structure and optimizing current conduction, but also can more efficiently transfer charge in the process of charge and discharge, improve electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, and more specifically, to a polycrystalline high-nickel ternary cathode material, its preparation method, and its application. Background Technology

[0002] High-nickel ternary materials (such as NCM811 and NCM90) are high-energy-density cathode materials in the lithium nickel cobalt manganese oxide system and are widely used in power batteries for new energy vehicles. In recent years, with technological advancements and growing market demand, high-nickel ternary materials have made significant progress in performance.

[0003] However, high-nickel ternary cathode materials exhibit volume expansion and contraction during cycling. The higher the nickel content, the more severe this phenomenon becomes, leading to a large number of cracks in the material in the later stages of cycling and premature battery failure.

[0004] In view of this, the present invention is proposed. Summary of the Invention

[0005] The purpose of this invention is to provide a polycrystalline high-nickel ternary cathode material, its preparation method, and its application, so as to solve or improve the above-mentioned technical problems.

[0006] This invention can be implemented as follows: In a first aspect, the present invention provides a polycrystalline high-nickel ternary cathode material, the polycrystalline high-nickel ternary cathode material comprising a polycrystalline high-nickel ternary cathode material body, at least a portion of the surface and at least a portion of the internal region of the polycrystalline high-nickel ternary cathode material body having pores, and at least the surface of the polycrystalline high-nickel ternary cathode material body having a conductive agent.

[0007] In an optional embodiment, the polycrystalline high-nickel ternary cathode material also has at least one of the following characteristics: Feature 1: The general formula of the polycrystalline high-nickel ternary cathode material is LiNi. x Co y Mn z O2, where x≥0.6, y≥0, z≥0, x+y+z=1; Feature 2: The conductive agent includes at least one of carbon nanotubes, flake graphite, conductive fibers, and amorphous carbon; Feature 3: Dv of polycrystalline high-nickel ternary cathode material 50 The thickness ranges from 7μm to 12μm. Feature 4: The porosity of polycrystalline high-nickel ternary cathode material is 1.5%~3.5%; Feature 5: The pore size of the internal region of the polycrystalline high-nickel ternary cathode material is 0.2μm~1.0μm; Feature 6: The lithium-nickel mixture ratio in polycrystalline high-nickel ternary cathode materials is 1.89%~1.96%; Feature 7: The specific surface area of ​​the polycrystalline high-nickel ternary cathode material is 0.95 m². 2 / g~1.05m 2 / g; Feature 8: Dn of polycrystalline high-nickel ternary cathode material 10 The thickness is 3.30μm~3.35μm; Feature 9: The carbon content of the polycrystalline high-nickel ternary cathode material is 1%~3%.

[0008] Secondly, the present invention provides a method for preparing a polycrystalline high-nickel ternary cathode material as described in the foregoing embodiments, comprising the following steps: mixing a nickel-cobalt-manganese hydroxide precursor doped with a pore-forming agent with a lithium-containing compound, followed by calcination to obtain a first intermediate material; cleaning the first intermediate material with a water washing solution, followed by solid-liquid separation and drying to obtain a second intermediate material; mixing the second intermediate material with a carbon source for forming a conductive agent, and sintering to obtain a polycrystalline high-nickel ternary cathode material.

[0009] In an optional embodiment, the preparation of a nickel cobalt manganese hydroxide precursor doped with a pore-forming agent includes: mixing a suspension of the nickel cobalt manganese hydroxide precursor with a pore-forming agent solution, and then carrying out an ion exchange reaction under conditions of a temperature of 40°C to 80°C, a pH of 10.0 to 11.0, and an ammonia concentration of 4 g / L to 8 g / L.

[0010] In an optional implementation, the ion exchange reaction time is 3h to 10h.

[0011] In an optional embodiment, the volume ratio of the suspension to the pore-forming agent solution is 1:1 to 1:4, wherein the concentration of the nickel cobalt manganese hydroxide precursor in the suspension is 100 g / L to 800 g / L, and the concentration of the pore-forming agent in the pore-forming agent solution is 0.01 g / L to 0.1 g / L.

[0012] In an optional embodiment, the concentration of the pore-forming agent in the pore-forming agent solution is 0.02 g / L to 0.05 g / L.

[0013] In an optional embodiment, the pore-forming agent includes at least one of a metal sulfate and a metal hydrochloride.

[0014] In an optional embodiment, the pore-forming agent includes at least one of potassium sulfate, sodium sulfate, lithium sulfate, aluminum sulfate, cobalt sulfate, manganese sulfate, nickel sulfate, zinc sulfate, copper sulfate, ferric sulfate, potassium chloride, sodium chloride, lithium chloride, aluminum chloride, cobalt chloride, manganese chloride, nickel chloride, zinc chloride, copper chloride, and ferric chloride.

[0015] In an optional embodiment, the preparation of the first intermediate material includes at least one of the following features: Feature 10: The lithium-containing compound includes at least one of lithium oxalate, lithium carbonate, lithium hydroxide monohydrate, lithium acetate, and lithium citrate; Feature 11: The ratio of the total molar amount of nickel, cobalt, and manganese in the nickel-cobalt-manganese hydroxide precursor doped with a pore-forming agent to the molar amount of lithium in the lithium-containing compound is 1:1 to 1:1.2. Feature 12: Calcination includes: first stage calcination at 300℃~750℃, second stage calcination at 800℃~1100℃, and third stage calcination at 500℃~750℃.

[0016] In an optional implementation, the holding time for the first stage of calcination is 3h to 10h, the holding time for the second stage of calcination is no more than 10h, and the holding time for the third stage of calcination is 10h to 15h.

[0017] In an optional embodiment, the preparation of the second intermediate material includes at least one of the following features: Feature 13: The washing solution is an aqueous solution of a metal salt, and the concentration of the metal salt in the washing solution is 500g / 3L to 1500g / 3L; the mass ratio of the metal salt to the first intermediate material in the washing solution is 1:2 to 1:10; Feature 14: The washing solution is an aqueous solution of a metal salt, wherein the anion of the metal salt in the aqueous solution is the same as the anion of the pore-forming agent in the pore-forming agent solution; preferably, the metal salt includes at least one of potassium sulfate, sodium sulfate, lithium sulfate, aluminum sulfate, cobalt sulfate, manganese sulfate, nickel sulfate, zinc sulfate, copper sulfate, and ferric sulfate; Feature 15: The temperature of the washing solution is 1.5℃~20℃; Feature 16: Drying temperature is 100℃~180℃, and drying time is 2h~20h.

[0018] In an optional embodiment, the preparation of the polycrystalline high-nickel ternary cathode material includes at least one of the following features: Feature 17: The mass ratio of the second intermediate material to the conductive agent is 3:0.05 to 3:0.1; Feature 18: Glucose is applied to a second intermediate material in solution form by spraying, and then sintered to form amorphous carbon; Feature 19: Sintering temperature is 200℃~500℃, sintering time is 3h~15h.

[0019] Thirdly, the present invention provides a battery containing a polycrystalline high-nickel ternary cathode material according to any of the foregoing embodiments.

[0020] Fourthly, the present invention provides an electrical device comprising the battery of the aforementioned embodiments.

[0021] The beneficial effects of this invention include: The polycrystalline high-nickel ternary cathode material provided by this invention contains pores that allow space for expansion during cycling, reducing material breakage and enhancing cycling performance. In addition, the conductive agent is present at least on the surface of the polycrystalline high-nickel ternary cathode material, which not only helps stabilize the structure and optimize current conduction, but also enables more efficient charge transfer and improved electrochemical performance during charging and discharging. Attached Figure Description

[0022] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 SEM image of the surface of the polycrystalline high-nickel ternary cathode material prepared in Example 1; Figure 2 SEM image of the cross-section of the polycrystalline high-nickel ternary cathode material prepared in Example 1; Figure 3 The image shows the XRD pattern of the polycrystalline high-nickel ternary cathode material prepared in Example 1. Figure 4 The graph shows the cycle capacity retention of the batteries corresponding to the ternary cathode materials provided in Examples 1-2 and Comparative Examples 4-6. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0025] The following is a detailed description of the polycrystalline high-nickel ternary cathode material, its preparation method, and its application provided by this invention.

[0026] The present invention provides a polycrystalline high-nickel ternary cathode material, which includes a polycrystalline high-nickel ternary cathode material body, at least a portion of the surface and at least a portion of the internal region of the polycrystalline high-nickel ternary cathode material body having pores, and at least the surface of the polycrystalline high-nickel ternary cathode material body having a conductive agent.

[0027] The pores in this polycrystalline high-nickel ternary cathode material allow space for expansion during cycling, reducing material breakage and enhancing cycling performance. In addition, the conductive agent is present at least on the surface of the polycrystalline high-nickel ternary cathode material, which not only helps stabilize the structure and optimize current conduction, but also enables more efficient charge transfer during charging and discharging, thus improving electrochemical performance.

[0028] In some alternative implementations, the general formula for the polycrystalline high-nickel ternary cathode material bulk can be LiNi. x Co y Mn z O2, where x≥0.6, y≥0, z≥0, x+y+z=1.

[0029] In some alternative embodiments, the conductive agent may, by way of example but not limitation, include at least one of carbon nanotubes, flake graphite, conductive fibers and amorphous carbon.

[0030] In some alternative implementations, the Dv of this polycrystalline high-nickel ternary cathode material 50 It can be 7μm~12μm, such as 7μm, 8μm, 9μm, 10μm, 11μm or 12μm, or other values ​​in the range of 7μm~12μm, such as 10μm~10.38μm.

[0031] In some alternative embodiments, the D of the polycrystalline high-nickel ternary cathode material n10 It can be 3.30μm~3.35μm.

[0032] The aforementioned "Dv" 50 "Dn10" refers to the volume distribution, specifically the particle size value when the cumulative particle size distribution reaches 50%; "Dn10" refers to the quantitative distribution, which is the diameter of the top 10% of particles when arranged from smallest to largest in the particle sample.

[0033] In some alternative embodiments, the porosity of the polycrystalline high-nickel ternary cathode material can be 1.5% to 3.5%, such as 1.5%, 2%, 2.5%, 3% or 3.5%, or other values ​​in the range of 1.5% to 3.5%, such as 1.63% to 1.87%.

[0034] If the porosity is less than 1.5%, it is not conducive to mitigating the volume expansion during material cycling; if the porosity is greater than 3.5%, it is not conducive to maintaining the structural stability of the material during cycling.

[0035] In some optional embodiments, the pore size corresponding to the pores in the internal region of the polycrystalline high-nickel ternary cathode material can be 0.2μm to 1.0μm.

[0036] By controlling the pore size within the aforementioned range, premature material failure during cycling can be prevented.

[0037] In some alternative implementations, the lithium-nickel mixture ratio of the polycrystalline high-nickel ternary cathode material is 1.89% to 1.96%, which is beneficial for the material to remain stable during cycling.

[0038] In some alternative embodiments, the specific surface area of ​​the polycrystalline high-nickel ternary cathode material is 0.95 m². 2 / g~1.05m 2 / g helps reduce side reactions that occur during material recycling.

[0039] In some alternative embodiments, the carbon content of the polycrystalline high-nickel ternary cathode material is 1% to 3%, which is beneficial to enhancing the conductivity of the material.

[0040] Accordingly, the present invention also provides a method for preparing the above-mentioned polycrystalline high-nickel ternary cathode material, comprising the following steps: mixing a nickel-cobalt-manganese hydroxide precursor doped with a pore-forming agent with a lithium-containing compound, followed by calcination to obtain a first intermediate material; cleaning the first intermediate material with a water washing solution, followed by solid-liquid separation and drying to obtain a second intermediate material; mixing the second intermediate material with a carbon source for forming a conductive agent, and sintering to obtain the polycrystalline high-nickel ternary cathode material.

[0041] In some optional embodiments, the preparation of a nickel-cobalt-manganese hydroxide precursor doped with a pore-forming agent may include: mixing a suspension of the nickel-cobalt-manganese hydroxide precursor with a pore-forming agent solution, followed by an ion exchange reaction at a temperature of 40°C to 80°C, a pH of 10.0 to 11.0, and an ammonia concentration of 4 g / L to 8 g / L. During the above process, the ammonia concentration of the ion exchange reaction can be adjusted by adding ammonia water, and the pH value of the ion exchange reaction can be adjusted by adding alkali solution.

[0042] The general formula of the nickel-cobalt-manganese hydroxide precursor is Ni. x Co y Mn z (OH)₂, x≥0.6, y≥0, z≥0, x+y+z=1. This nickel-cobalt-manganese hydroxide precursor can be purchased directly or prepared by referring to existing techniques in the art. A suspension of the nickel-cobalt-manganese hydroxide precursor is obtained by dispersing it in water. For example, the concentration of the nickel-cobalt-manganese hydroxide precursor in the suspension can be 100 g / L to 800 g / L.

[0043] The volume ratio of the suspension to the pore-forming agent solution can be from 1:1 to 1:4, such as 1:1, 1:2, 1:3, or 1:4, or other values ​​within the range of 1:1 to 1:4. The concentration of the pore-forming agent in the pore-forming agent solution can be from 0.01 g / L to 0.1 g / L, such as 0.01 g / L, 0.02 g / L, 0.05 g / L, or 0.1 g / L, or other values ​​within the range of 0.01 g / L to 0.1 g / L. In some optional embodiments, the concentration of the pore-forming agent in the pore-forming agent solution can be from 0.02 g / L to 0.05 g / L.

[0044] The amount of pore-forming agent used is directly related to the porosity of the final material. If the amount of pore-forming agent is too small, the porosity of the polycrystalline high-nickel ternary cathode material will be too low; if the amount of pore-forming agent is too large, the porosity of the polycrystalline high-nickel ternary cathode material will be too high.

[0045] In some alternative embodiments, the pore-forming agent may include at least one of metal sulfates and metal hydrochlorides. For example, the pore-forming agent may include at least one of potassium sulfate, sodium sulfate, lithium sulfate, aluminum sulfate, cobalt sulfate, manganese sulfate, nickel sulfate, zinc sulfate, copper sulfate, ferric sulfate, potassium chloride, sodium chloride, lithium chloride, aluminum chloride, cobalt chloride, manganese chloride, nickel chloride, zinc chloride, copper chloride, and ferric chloride.

[0046] In some alternative embodiments, the temperature of the ion exchange reaction can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, or 80°C, or other values ​​within the range of 40°C to 80°C.

[0047] The pH value for ion exchange reactions can be 10, 10.2, 10.5, 10.8 or 11, or other values ​​in the range of 10.0 to 11.0.

[0048] The ammonia concentration for ion exchange reactions can be 4 g / L, 5 g / L, 6 g / L, 7 g / L, or 8 g / L, or other values ​​within the range of 4 g / L to 8 g / L.

[0049] The time for ion exchange reactions can be 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, or other values ​​within the range of 3h to 10h.

[0050] By subjecting a suspension of nickel cobalt manganese hydroxide precursor to an ion exchange reaction with a pore-forming agent solution under the above conditions, a nickel cobalt manganese hydroxide precursor with a surface-doped pore-forming agent can be obtained.

[0051] In some alternative embodiments, the lithium-containing compound may exemplary include at least one of lithium oxalate, lithium carbonate, lithium hydroxide monohydrate, lithium acetate, and lithium citrate.

[0052] The ratio of the total molar amount of nickel, cobalt, and manganese in the nickel-cobalt-manganese hydroxide precursor doped with a pore-forming agent to the molar amount of lithium in the lithium-containing compound can be from 1:1 to 1:1.2, such as 1:1, 1:1.1, or 1:1.2, or other values ​​within the range of 1:1 to 1:1.2.

[0053] In some optional embodiments, calcination includes: a first stage of calcination at 300°C to 750°C (e.g., 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, or 750°C), a second stage of calcination at 800°C to 1100°C (e.g., 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, or 1100°C), and a third stage of calcination at 500°C to 750°C (e.g., 500°C, 550°C, 600°C, 650°C, 700°C, or 750°C). The above process can be carried out in an oxygen atmosphere.

[0054] The holding time for the first stage of calcination can be 3h to 10h (e.g., 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, etc.), the holding time for the second stage of calcination should not exceed 10h (e.g., 1h, 2h, 4h, 6h, 8h or 10h, etc.), and the holding time for the third stage of calcination should be 10h to 15h (e.g., 10h, 11h, 12h, 13h, 14h or 15h, etc.).

[0055] The above calcination process is divided into three stages. The first stage mainly serves to dehydrate the precursor and lithium source, the second stage mainly serves to accelerate the reaction between the precursor and lithium source, and the third stage mainly serves to enhance the crystallinity of the material.

[0056] The heating rate during the calcination process can be 5°C / min to quickly reach the target temperature, allowing the surface-doped pore-forming agent to further penetrate into the nickel-cobalt-manganese hydroxide precursor. Furthermore, at the high temperature of the second stage, the pore-forming agent fuses with the material and inhibits primary particle contact, thereby forming pores on and within the surface of the first intermediate material. In addition, the calcination process through these three stages ensures that the primary particle size of the first intermediate material is within a suitable range, which helps to ensure that the material has optimal capacity.

[0057] In some optional embodiments, the washing solution used to wash the first intermediate material is an aqueous solution of a metal salt. The concentration of the metal salt in the washing solution can be from 500 g / 3 L to 1500 g / 3 L, such as 500 g / 3 L, 1000 g / 3 L, or 1500 g / 3 L. The mass ratio of the metal salt to the first intermediate material in the washing solution can be from 1:2 to 1:10, such as 1:2, 1:5, 1:8, or 1:10.

[0058] The anion of the metal salt in the above-mentioned aqueous solution is the same as the anion of the pore-forming agent in the pore-forming agent solution. For example, the metal salt in the aqueous solution may include at least one of potassium sulfate, sodium sulfate, lithium sulfate, aluminum sulfate, cobalt sulfate, manganese sulfate, nickel sulfate, zinc sulfate, copper sulfate, and ferric sulfate.

[0059] In some alternative embodiments, the temperature of the washing solution can be 1.5℃ to 20℃, such as 1.5℃, 5℃, 10℃, 15℃ or 20℃, or other values ​​within the range of 1.5℃ to 20℃.

[0060] If the temperature of the above-mentioned washing solution is higher than 20°C, it can easily lead to excessive lithium extraction from the material.

[0061] After the washing solution is mixed with the first intermediate material, it is stirred for 10 min to 60 min, then centrifuged in a centrifuge at 45 Hz to 55 Hz for 0.5 h to 1.5 h, and then dried in a vacuum drying oven.

[0062] In some alternative embodiments, the drying temperature can be 100°C to 180°C, such as 100°C, 120°C, 150°C or 180°C, or other values ​​within the range of 100°C to 180°C.

[0063] In some alternative implementations, the drying time can be 2h to 20h, such as 2h, 5h, 10h, 15h or 20h, or other values ​​within the range of 2h to 20h.

[0064] This invention removes residual or excess pore-forming agent by washing the first intermediate material with a water washing solution, preventing the pore-forming agent from remaining inside the first intermediate material and affecting its capacity. However, if pure water is used for washing, the pore-forming agent will rapidly leave the material, thereby weakening the interparticle bonding force on the material surface and causing powdering. Therefore, this invention specifically adds a specific metal salt to the water to form a metal salt aqueous solution. The anions in this metal salt are the same as those in the pore-forming agent, and the cations in this metal salt can be deposited on the material surface. The anions, being the same as those in the pore-forming agent, slow down the dissolution rate of the pore-forming agent inside the material, controlling the water washing rate to maintain a relatively balanced state and preventing structural collapse; the cations can contact the residual alkali on the material surface and deposit there, providing a protective effect and reducing powdering. The reaction equation between the cations and the residual alkali includes: M n+ +nOH - =M(OH) n ↓; M n+ +0.5nCO3 2- =M(CO3) 0.5n↓; where "M" represents a cation.

[0065] In some alternative embodiments, the mass ratio of the second intermediate material to the conductive agent can be 3:0.05 to 3:0.1, such as 3:0.05, 3:0.075 or 3:0.1.

[0066] In some alternative embodiments, glucose is applied to the second intermediate material in solution form by spraying, for example, at least onto the surface of the material, and further possibly into the pores of the material, and then sintered to form amorphous carbon. For example, 50g to 250g of glucose can be dissolved in 100mL to 500mL of deionized water to obtain a glucose solution; the glucose solution is then uniformly sprayed onto the second intermediate material using a spraying device.

[0067] In some alternative embodiments, the sintering temperature can be 200℃~500℃, such as 200℃, 250℃, 300℃, 350℃, 400℃, 450℃ or 500℃, or other values ​​within the range of 200℃~500℃.

[0068] The sintering time can be 3h to 15h, such as 3h, 5h, 8h, 10h, 12h or 15h, or other values ​​within the range of 3h to 15h.

[0069] By attaching glucose, which is used to form amorphous carbon, to at least the surface of the material and then carbonizing it after high-temperature sintering, the conductivity of polycrystalline high-nickel ternary materials can be improved while stabilizing the structure, thereby improving the overall performance of the battery.

[0070] In addition, the present invention also provides a battery cell, wherein the positive electrode material of the battery cell includes the above-mentioned polycrystalline high-nickel ternary positive electrode material.

[0071] The above sintering process can be carried out in an oxygen-free atmosphere (such as a nitrogen atmosphere).

[0072] For example, the aforementioned battery cells can be used, but are not limited to, in electrical devices such as vehicles, ships, or aircraft.

[0073] The present invention also provides a battery comprising the above-described battery cells, which has superior cycle performance.

[0074] The present invention also provides an electrical device comprising the aforementioned battery cell and / or battery. As examples, the electrical device may include, but is not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Electric toys may include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc., while spacecraft may include airplanes, rockets, space shuttles, and spacecraft, etc.

[0075] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0076] Example 1 This embodiment provides a polycrystalline high-nickel ternary cathode material, the preparation method of which includes: Step (1): Ni cobalt manganese hydroxide precursor Ni 0.94 Co 0.03 Mn 0.03 (OH)₂ was dispersed in water to obtain a suspension of nickel-cobalt-manganese hydroxide precursor with a concentration of 300 g / L. The suspension was mixed with a pore-forming agent solution (lithium sulfate, concentration 0.05 g / L) at a volume ratio of 1:1, and then subjected to an ion exchange reaction for 6 h at 60 °C, pH 10.6, and ammonia concentration of 5 g / L to obtain a nickel-cobalt-manganese hydroxide precursor Ni doped with the pore-forming agent. 0.94 Co 0.03 Mn 0.03 L 0.035 (OH)2. In the above process, the ammonia concentration for the ion exchange reaction is adjusted by adding ammonia water, and the pH value for the coprecipitation reaction is adjusted by adding alkali solution.

[0077] Step (2): Take 4 kg of the nickel-cobalt-manganese hydroxide precursor with surface-doped pore-forming agent and mix it with 2.03 kg of lithium-containing compound (lithium hydroxide monohydrate) by dry ball milling for 5 h to obtain a mixture. The ratio of the total molar amount of nickel, cobalt, and manganese in the nickel-cobalt-manganese hydroxide precursor with surface-doped pore-forming agent to the molar amount of lithium in the lithium-containing compound is 1:1.15. The mixture is then calcined in an oxygen atmosphere at 700°C for 9 h, followed by calcination at 900°C for 2 h, and then calcined at 700°C for 10 h. The heating and cooling rates are both 5°C / min to obtain the first intermediate material.

[0078] Step (3): Take 2.4L of deionized water at 1.5℃, add 800g of aluminum sulfate octadecahydrate, stir with a mechanical stirrer at 200rpm for 10min to obtain a water washing solution; add 4kg of the first intermediate material to the water washing solution, stir for 10min, place it in a centrifuge, centrifuge at 50Hz for 1h, and then place it in a vacuum drying oven to dry at 120℃ for 10h. After the material is completely dry, pass it through a 200-mesh sieve to obtain the second intermediate material.

[0079] Step (4): Dissolve 75g of glucose in 150mL of deionized water, and then use a spraying device to spray it evenly on the surface and pores of 3kg of the second intermediate material. Finally, sinter at 450℃ for 10h under a nitrogen atmosphere to obtain polycrystalline high-nickel ternary cathode material.

[0080] Example 2 The difference between this embodiment and embodiment 1 is that in step (2), the mixture is first calcined at 700°C for 9 hours in an oxygen atmosphere, then calcined at 880°C for 2 hours in a second stage, and then calcined at 700°C for 10 hours in a third stage. The heating rate and cooling rate are both 5°C / min, and the first intermediate material is obtained.

[0081] Example 3 This embodiment provides a polycrystalline high-nickel ternary cathode material, the preparation method of which includes: Step (1): Ni cobalt manganese hydroxide precursor Ni 0.94 Co 0.03 Mn 0.03 (OH)₂ was dispersed in water to obtain a suspension of nickel-cobalt-manganese hydroxide precursor with a concentration of 300 g / L. The suspension was mixed with a pore-forming agent solution (potassium chloride, concentration 0.02 g / L) at a volume ratio of 1:4, and then subjected to an ion exchange reaction for 10 h at 40 °C, pH 10.0, and ammonia concentration of 4 g / L to obtain a nickel-cobalt-manganese hydroxide precursor with a surface-doped pore-forming agent. During the above process, the ammonia concentration for the ion exchange reaction was adjusted by adding ammonia water, and the pH value for the ion exchange reaction was adjusted by adding alkali solution.

[0082] Step (2): The nickel-cobalt-manganese hydroxide precursor with surface-doped pore-forming agent was mixed with a lithium-containing compound (lithium oxalate) by dry ball milling for 5 hours to obtain a mixture. The ratio of the total molar amount of nickel, cobalt, and manganese in the nickel-cobalt-manganese hydroxide precursor with surface-doped pore-forming agent to the molar amount of lithium in the lithium-containing compound was 1:1. The mixture was then calcined in an oxygen atmosphere at 300°C for 10 hours, followed by 750°C for 10 hours, and then 500°C for 15 hours. The heating and cooling rates were both 5°C / min to obtain the first intermediate material.

[0083] Step (3): Take deionized water at 10℃, add sodium chloride, and stir with a mechanical stirrer at 200 rpm for 10 min to obtain a water washing solution; add the first intermediate material to the water washing solution, stir for 10 min, and then place it in a centrifuge at 50 Hz for 1 h, followed by drying in a vacuum drying oven at 100℃ for 20 h. After the material is completely dry, pass it through a 200-mesh sieve to obtain the second intermediate material. The concentration of the metal salt in the water washing solution is 500 g / 3 L, and the mass ratio of the metal salt to the first intermediate material in the water washing solution is 1:2.

[0084] Step (4): Dissolve 50g of glucose in 100mL of deionized water, then spray it evenly onto the surface and pores of the second intermediate material using a spray device. Finally, sinter the mixture at 200℃ for 15h under a nitrogen atmosphere to obtain a polycrystalline high-nickel ternary cathode material. The mass ratio of the second intermediate material to the conductive agent is 3:0.05.

[0085] Example 4 This embodiment provides a polycrystalline high-nickel ternary cathode material, the preparation method of which includes: Step (1): Ni cobalt manganese hydroxide precursor Ni 0.94 Co 0.03 Mn 0.03 (OH)₂ was dispersed in water to obtain a suspension of nickel-cobalt-manganese hydroxide precursor with a concentration of 300 g / L. The suspension was mixed with a pore-forming agent solution (manganese sulfate, concentration 0.1 g / L) at a volume ratio of 1:2, and then subjected to an ion exchange reaction for 3 h at 80 °C, pH 11, and ammonia concentration of 8 g / L to obtain a nickel-cobalt-manganese hydroxide precursor with a surface-doped pore-forming agent. During the above process, the ammonia concentration for the ion exchange reaction was adjusted by adding ammonia water, and the pH value for the ion exchange reaction was adjusted by adding alkali solution.

[0086] Step (2): The nickel-cobalt-manganese hydroxide precursor with surface-doped pore-forming agent was mixed with a lithium-containing compound (lithium citrate) by dry ball milling for 5 hours to obtain a mixture. The molar ratio of the nickel-cobalt-manganese hydroxide precursor with surface-doped pore-forming agent to the lithium element in the lithium-containing compound was 1:2. The mixture was then calcined in an oxygen atmosphere at 750°C for 3 hours, followed by a second stage calcination at 1100°C for 5 hours, and a third stage calcination at 750°C for 10 hours. The heating and cooling rates were both 5°C / min to obtain the first intermediate material.

[0087] Step (3): Take deionized water at 20℃, add manganese sulfate, and stir with a mechanical stirrer at 200 rpm for 10 min to obtain a water washing solution; add the first intermediate material to the water washing solution, stir for 10 min, and then place it in a centrifuge and centrifuge at 50 Hz for 1 h, and then place it in a vacuum drying oven and dry at 180℃ for 2 h. After the material is completely dry, pass it through a 200-mesh sieve to obtain the second intermediate material. The concentration of the metal salt in the water washing solution is 1500 g / 3 L, and the mass ratio of the metal salt in the water washing solution to the first intermediate material is 1:10.

[0088] Step (4): Dissolve 250g of glucose in 500mL of deionized water, then spray it evenly onto the surface and pores of the second intermediate material using a spray device. Finally, sinter the mixture at 500℃ for 3 hours under a nitrogen atmosphere to obtain a polycrystalline high-nickel ternary cathode material. The mass ratio of the second intermediate material to the conductive agent is 3:0.1.

[0089] Comparative Example 1 The difference between this comparative example and Example 1 is that in step (2), calcination is carried out only in an oxygen atmosphere, with a heating rate of 5°C / min to 700°C and held for 20 hours.

[0090] Comparative Example 2 The difference between this comparative example and Example 1 is that in step (2), calcination is carried out only in an oxygen atmosphere, with a heating rate of 5°C / min to 900°C and held for 20 hours.

[0091] Comparative Example 3 This comparative example is the first intermediate material obtained in step (2) of Example 1.

[0092] Comparative Example 4 This comparative example provides a ternary cathode material, the preparation method of which includes: Step (1): Take 4 kg of nickel-cobalt-manganese hydroxide precursor Ni 0.94 Co 0.03 Mn 0.03(OH)₂ was mixed with 2.03 kg of a lithium-containing compound (lithium hydroxide monohydrate) by dry ball milling for 5 h to obtain a mixture. The mixture was then subjected to a first-stage calcination at 700 °C for 9 h in an oxygen atmosphere, followed by a second-stage calcination at 900 °C for 2 h, and a third-stage calcination at 700 °C for 10 h, with a heating and cooling rate of 5 °C / min, to obtain an intermediate material.

[0093] Step (2): Take 2.4L of deionized water at 0.5℃, add 800g of aluminum sulfate octadecahydrate, stir with a mechanical stirrer at 200rpm for 10min to obtain a water washing solution; add 4kg of intermediate material to the water washing solution, stir for 10min, place in a centrifuge, centrifuge at 50Hz for 1h, and then place in a vacuum drying oven to dry at 120℃ for 10h. After the material is completely dry, pass through a 200-mesh sieve to obtain ternary cathode material.

[0094] That is, no pores were created in the precursor in this comparative example, and no conductive agent was used.

[0095] Comparative Example 5 The difference between this comparative example and Example 1 is that in step (3), pure water is used to clean the first intermediate material.

[0096] Comparative Example 6 The difference between this comparative example and Example 1 is that in step (1), the volume ratio of the suspension to the pore-forming agent solution is 1:0.5.

[0097] Comparative Example 7 The difference between this comparative example and Example 1 is that in step (1), the volume ratio of the suspension to the pore-forming agent solution is 1:5.

[0098] Test case (1) The polycrystalline high-nickel ternary cathode material prepared in Example 1 was characterized by SEM and XRD, and the results are as follows: Figures 1 to 3 As shown.

[0099] Figure 1 and Figure 2 The ternary cathode material prepared from the nickel-cobalt-manganese hydroxide precursor doped with a pore-forming agent has pores on both its surface and inside.

[0100] Depend on Figure 3 It can be seen that glucose carbonizes the material surface without reducing lithium nickel cobalt manganese oxide, and no impurity peaks appear in the XRD data.

[0101] (2) The performance of the ternary cathode materials prepared in Examples 1-4 and Comparative Examples 1-7 was tested, and the results are shown in Table 1 and... Figure 4 As shown.

[0102] Porosity was measured using ImageJ software, lithium-nickel hybridization was determined by XRD pattern analysis using Jade 6.0 software, specific surface area (BET) was measured using a specific surface area analyzer, and particle size Dn was measured. 10 and D 50 All values ​​were measured using a particle size analyzer, and the carbon content was measured using a carbon-sulfur analyzer.

[0103] The discharge capacity was obtained by preparing a battery using various ternary cathode materials in the following manner and then testing it. The battery preparation method is as follows: High-nickel ternary cathode materials were used as active materials, acetylene black as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder, weighed in a mass ratio of 90:5:5 to form electrode sheets. Using these electrode sheets as the positive electrode and lithium metal sheets as the negative electrode, CR2430 button batteries were assembled in a glove box filled with high-purity argon gas. The capacity testing conditions included: using a Blue Electric Tester (CT2001A) to test the electrical performance of the assembled batteries under the following conditions: 2.8V~4.3V, 0.1C (1C=220mA / g) for 1 cycle and 80 cycles.

[0104] Table 1 Performance Data

[0105] As can be seen from Table 1: Examples 1-4 all use nickel-cobalt-manganese hydroxide precursors with surface-doped pore-forming agents. Under rapid calcination, the pore-forming agents penetrate into the material, creating numerous pores on the material surface and inside. A specific metal salt solution is used to wash away the pore-forming agents inside the material, while depositing them on the material surface to provide protection and reduce primary particle detachment. After water washing, a glucose solution is sprayed on, followed by sintering and carbonization. This stabilizes the structure and improves the conductivity of the polycrystalline high-nickel ternary material, resulting in batteries corresponding to the polycrystalline high-nickel ternary cathode materials of Examples 1-4 having higher discharge capacity and better cycle performance.

[0106] Comparing Example 1 and Comparative Example 1, since the pore-forming agent has a high melting point, Comparative Example 1, using a normal sintering temperature, failed to create pores inside the material, and the capacity was not improved.

[0107] By comparing Example 1 and Comparative Example 2, Comparative Example 2 uses a temperature higher than the melting point of the pore-forming agent, which can create pores inside the material. However, due to the excessively high sintering temperature and the excessively large primary particles, the material's capacity is severely affected.

[0108] Comparing Example 1 and Comparative Example 3, Comparative Example 3 did not remove the sulfate ions introduced for pore formation. Excessive sulfate impurities within the material hindered lithium ion insertion and extraction during the charging and discharging process, resulting in a significantly lower capacity. Although no carbon coating was applied in Comparative Example 3, residual lithium on the material surface reacted with CO2 in the air, leading to the detection of carbon content.

[0109] Comparing Example 1 and Comparative Example 4, Comparative Example 4, which uses short-time high-temperature sintering, shows a significantly lower degree of lithium-nickel mixing compared to the comparative example using a single sintering platform. No pore-forming agent was added during the sintering process, resulting in a lack of pores within the material. This hinders lithium-ion insertion and extraction during the charging and discharging process, leading to a relatively low capacity. Furthermore, the lack of pores also causes excessive internal stress during cycling, resulting in mediocre cycling performance.

[0110] By comparing Example 1 and Comparative Example 5, Comparative Example 5 used water to wash the material. Due to the lack of anionic sulfate ions in the water, which are the same as those in the pore-forming agent, and the absence of cations that could be deposited on the material surface, the material experienced severe primary particle detachment, and the Dn10 was significantly smaller. Although the capacity was relatively high, the excessive micropowder deteriorated the cycle performance.

[0111] By comparing Example 1 and Comparative Examples 6-7, it was found that both excessively low and excessively high volume ratios of suspension to pore-forming agent solution would reduce the discharge capacity of batteries prepared from the corresponding ternary cathode materials.

[0112] In summary, the polycrystalline high-nickel ternary cathode material provided by this invention contains pores that allow space for expansion during cycling, reducing material breakage and enhancing cycling performance. Furthermore, the conductive agent is present at least on the surface of the polycrystalline high-nickel ternary cathode material, which not only helps stabilize the structure and optimize current conduction, but also enables more efficient charge transfer and improved electrochemical performance during charging and discharging.

[0113] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A polycrystalline high-nickel ternary cathode material, characterized in that, The polycrystalline high-nickel ternary cathode material includes a polycrystalline high-nickel ternary cathode material body, at least a portion of the surface and at least a portion of the internal region of the polycrystalline high-nickel ternary cathode material body having pores, and at least the surface of the polycrystalline high-nickel ternary cathode material body having a conductive agent. The preparation of the polycrystalline high-nickel ternary cathode material includes the following steps: mixing a nickel-cobalt-manganese hydroxide precursor with a surface-doped pore-forming agent with a lithium-containing compound, followed by calcination to obtain a first intermediate material; cleaning the first intermediate material with a water washing solution, followed by solid-liquid separation and drying to obtain a second intermediate material; mixing the second intermediate material with a carbon source for forming a conductive agent, and sintering to obtain the polycrystalline high-nickel ternary cathode material. The preparation of the nickel cobalt manganese hydroxide precursor with surface doped pore-forming agent includes: mixing a suspension of the nickel cobalt manganese hydroxide precursor with a pore-forming agent solution, and then carrying out an ion exchange reaction under the conditions of a temperature of 40℃~80℃, a pH value of 10.0~11.0, and an ammonia concentration of 4g / L~8g / L. The washing solution is an aqueous solution of a metal salt, and the anions of the metal salt in the aqueous solution are the same as the anions of the pore-forming agent in the pore-forming agent solution.

2. The polycrystalline high-nickel ternary cathode material according to claim 1, characterized in that, The polycrystalline high-nickel ternary cathode material also has at least one of the following characteristics: Feature 1: The general formula of the polycrystalline high-nickel ternary cathode material is LiNi. x Co y Mn z O2, where x≥0.6, y≥0, z≥0, x+y+z=1; Feature 2: The conductive agent includes at least one of carbon nanotubes, flake graphite, conductive fibers, and amorphous carbon; Feature 3: The Dv of the polycrystalline high-nickel ternary cathode material 50 The thickness ranges from 7μm to 12μm. Feature 4: The porosity of the polycrystalline high-nickel ternary cathode material is 1.5%~3.5%; Feature 5: The pore size of the pores in the internal region of the polycrystalline high-nickel ternary cathode material is 0.2μm~1.0μm; Feature 6: The lithium-nickel mixing ratio of the polycrystalline high-nickel ternary cathode material is 1.89%~1.96%; Feature 7: The specific surface area of ​​the polycrystalline high-nickel ternary cathode material is 0.95 m². 2 / g~1.05m 2 / g; Feature 8: The Dn of the polycrystalline high-nickel ternary cathode material 10 The thickness is 3.30μm~3.35μm; Feature 9: The carbon content of the polycrystalline high-nickel ternary cathode material is 1%~3%.

3. A method for preparing a polycrystalline high-nickel ternary cathode material as described in claim 1 or 2, characterized in that, The process includes the following steps: mixing a nickel-cobalt-manganese hydroxide precursor with a surface-doped pore-forming agent with a lithium-containing compound, followed by calcination to obtain a first intermediate material; The first intermediate material was washed with a water washing solution, followed by solid-liquid separation and drying to obtain the second intermediate material; The second intermediate material is mixed with a carbon source for forming a conductive agent and sintered to obtain a polycrystalline high-nickel ternary cathode material. The preparation of the nickel cobalt manganese hydroxide precursor with surface doped pore-forming agent includes: mixing a suspension of the nickel cobalt manganese hydroxide precursor with a pore-forming agent solution, and then carrying out an ion exchange reaction under the conditions of a temperature of 40℃~80℃, a pH value of 10.0~11.0, and an ammonia concentration of 4g / L~8g / L.

4. The preparation method according to claim 3, characterized in that, The ion exchange reaction takes 3 to 10 hours.

5. The preparation method according to claim 3 or 4, characterized in that, The volume ratio of the suspension to the pore-forming agent solution is 1:1 to 1:4, wherein the concentration of the nickel cobalt manganese hydroxide precursor in the suspension is 100 g / L to 800 g / L, and the concentration of the pore-forming agent in the pore-forming agent solution is 0.01 g / L to 0.1 g / L.

6. The preparation method according to claim 5, characterized in that, The concentration of the pore-forming agent in the pore-forming agent solution is 0.02 g / L to 0.05 g / L.

7. The preparation method according to claim 5, characterized in that, The pore-forming agent includes at least one of metal sulfate and metal hydrochloride.

8. The preparation method according to claim 7, characterized in that, The pore-forming agent includes at least one of potassium sulfate, sodium sulfate, lithium sulfate, aluminum sulfate, cobalt sulfate, manganese sulfate, nickel sulfate, zinc sulfate, copper sulfate, ferric sulfate, potassium chloride, sodium chloride, lithium chloride, aluminum chloride, cobalt chloride, manganese chloride, nickel chloride, zinc chloride, copper chloride, and ferric chloride.

9. The preparation method according to claim 3, characterized in that, The preparation of the first intermediate material includes at least one of the following features: Feature 10: The lithium-containing compound includes at least one of lithium oxalate, lithium carbonate, lithium hydroxide monohydrate, lithium acetate, and lithium citrate; Feature 11: The ratio of the total molar amount of nickel, cobalt, and manganese in the nickel-cobalt-manganese hydroxide precursor doped with the pore-forming agent to the molar amount of lithium in the lithium-containing compound is 1:1 to 1:1.2; Feature 12: The calcination includes: first stage calcination at 300℃~750℃, second stage calcination at 800℃~1100℃, and third stage calcination at 500℃~750℃.

10. The preparation method according to claim 9, characterized in that, The holding time for the first stage of calcination is 3 to 10 hours, the holding time for the second stage of calcination is no more than 10 hours, and the holding time for the third stage of calcination is 10 to 15 hours.

11. The preparation method according to claim 5, characterized in that, The preparation of the second intermediate material includes at least one of the following features: Feature 13: The washing solution is an aqueous solution of a metal salt, and the concentration of the metal salt in the washing solution is 500g / 3L to 1500g / 3L; the mass ratio of the metal salt to the first intermediate material in the washing solution is 1:2 to 1:10; Feature 14: The temperature of the washing solution is 1.5℃~20℃; Feature 15: Drying temperature is 100℃~180℃, and drying time is 2h~20h.

12. The preparation method according to claim 11, characterized in that, The metal salt includes at least one of potassium sulfate, sodium sulfate, lithium sulfate, aluminum sulfate, cobalt sulfate, manganese sulfate, nickel sulfate, zinc sulfate, copper sulfate, and ferric sulfate.

13. The preparation method according to claim 3, characterized in that, The preparation of the polycrystalline high-nickel ternary cathode material includes at least one of the following characteristics: Feature 16: The mass ratio of the second intermediate material to the conductive agent is 3:0.05 to 3:0.1; Feature 17: Glucose is applied to the second intermediate material in solution form by spraying, and then sintered to form amorphous carbon; Feature 18: Sintering temperature is 200℃~500℃, and sintering time is 3h~15h.

14. A battery, characterized in that, The battery contains the polycrystalline high-nickel ternary cathode material as described in claim 1 or 2.

15. An electrical appliance, characterized in that, The electrical device includes the battery as described in claim 14.

Citation Information

Patent Citations

  • A ternary cathode material with high conductivity and a preparation method thereof

    CN109244449A

  • Ternary polycrystalline positive electrode material, preparation method thereof and lithium ion battery

    CN120727759A